Sulfonate N‐Heterocyclic Carbene–Copper Complexes: Uniquely Effective Catalysts for Enantioselective Synthesis of C−C, C−B, C−H, and C−Si Bonds. Issue 48 (26th August 2020) - Hoveyda, Amir H.; Zhou, Yuebiao; Shi, Ying; Brown, M. Kevin; Wu, Hao; Torker, Sebastian
Abstract: A copper‐based complex that contains a sulfonate N‐heterocyclic carbene ligand was first reported 15 years ago. Since then, these organometallic entities have proven to be uniquely effective in catalyzing an assortment of enantioselective transformations, including allylic substitutions, conjugate additions, proto‐boryl additions to alkenes, boryl and silyl substitutions, hydride‐allyl additions to alkenyl boronates, and additions of boron‐containing allyl moieties to N‐H ketimines. In this review article, we detail the shortcomings in the state‐of‐the‐art that fueled the development of this air stable ligand class, members of which can be prepared on multigram scale. For each reaction type, when relevant, the prior art at the time of the advance involving sulfonate NHC‐Cu catalysts and/or subsequent key developments are briefly analyzed, and the relevance of the advance to efficient and enantioselective total or formal synthesis of biologically active molecules is underscored. Mechanistic analysis of the structural attributes of sulfonate NHC‐Cu catalysts that are responsible for their ability to facilitate transformations with high efficiency as well as regio‐ and enantioselectivity are detailed. This review contains several formerly undisclosed methodological advances and mechanistic analyses, the latter of which constitute a revision of previously reported proposals. Abstract : Catalysis by metal bridging: Sulfonate NHC–Cu catalysts promote a variety of transformations with uniquely high efficiency as well as regio‐, and enantioselectivity. The origins of the discovery of these chiral complexes, the process that they are adept at catalyzing, comparison with alternative approaches, and different applications to total synthesis are presented.